Open – Air Museum : showcasing the heritage treasure as ways of connecting people, history and nature at Pantai Melawi, Bachok, Kelantan - Ramli, Nurul Atikah (2018)
Malaysia is experiencing an incredible pace of tourism development where the cultural heritage is one of the crucial part that have contributed to appeal as the tourist destination and become economic sources. This paper addresses the heritage treasure where the societies can be captivated by the sense of belongings at Pantai Melawi, Bachok, Kelantan as it has the authenticity of both cultural and military heritage. However, the exposure of these both heritage towards societies is not highlighted adequately enough which leads to the degradation and abandoned of it. Hence, the purpose of this study is to preserve and remain the existing heritage treasure with the supports of local community as well as outsiders. With the aid of heritage asset’s presence, it can be showcased and helps in connecting people, history and nature at Pantai Melawi. The finding of this study is not only considered on how the both of military and cultural heritage will be preserved within its rural landscape, but also the proposal of an open – air museum at Pantai Melawi where enabling the village to be a destination of heritage tourism. Through the implementation of military ambience within historic space and provision of local tradition activities within local settlements, Pantai Melawi will be transformed into vibrant heritage area where it has its own identity and character.